The effect of using reciprocal and peer-tutoring styles in learning some motor skills for sport education lesson - وليد وعد الله علي; عبد السلام عبد الجبار (Journal of Sport Science Technology and Physical Activities, 2025)
The aim of the study was to explore the effect of using reciprocal and peer-tutoring styles in learning some motor skills for sport education lesson , and to compare between them in post test. -Experimental method was used to suit the nature of the study . popular of research consisted of (90) student , they represented the first stage in sport education section , nenaua education , in Iraq for the year (2007-2008) . Sample of the study consisted of (40) students , they divided into two equal experimental groups , each groups consisted of (20) students. -The first experimental group apply the reciprocal style , and the second experimental group apply the peer-tutoring style . - Learning program included the skills of (passing , juggling , and stationary shooting in basketball). -Equivalent was achieved among the two experimental group in (growth variables, some physical and motor components, basic skills in basketball. - statistical means were used to treat the results of the study. -Finally , the researcher concluded the following :- 1- Reciprocal and peer-tutoring styles were more effective in learning some basic skills in basketball. 2- Students of second experimental group , which they used peer-tutoring style were better than the students of first experimental group which they used reciprocal style in learning juggling and stationary shooting skills in basketball. 3- There was no significant differences between the two styles in learning the chest passing skill